Evaluation of frailty in individuals aged 65 years and over, with and without diabetes: A cross-sectional study - Karsli , Zuhre; Pamuk, Gulseren; Ongel , Kurtulus (Annals of Medical Research, 2022)
Aim: This study aims to reveal the effect of frailty in patients aged 65 years and over with and without type 2 diabetes. Materials and Methods: A total of 298 elderly individuals aged 65 and over, 149 type 2 diabetic individuals and 149 non-diabetic individuals as the control group, were included in the descriptive cross-sectional study. Both groups were surveyed using Edmonton Frail Scale and socio-demographic data questionnaire Results: The mean age of the participants was 70.68±5.45 years, and 63.4% (n=189) of participants were female. Of the diabetic patients, 61 (40.9%) patients were found to be frail, 41 (27.5%) to be prone to frailty, and 47 (31.5%) to be non-frail. In individuals without diabetes, 33 (22.1%) individuals were found to be frail, 22 (14.8%) to be prone to frailty, and 94 (63.1%) to be non-frail. When both groups were analyzed statistically in terms of frailty, it was observed that frailty increased significantly in diabetic patients (p<0.05). Conclusion: This study has proved that frailty increases in type 2 diabetic patients compared to non-diabetic patients, the perception and assessment of aging may play a role under frailty, and quality of life is one of the factors that should be considered in the development of frailty. The high rates of falling and hospitalization in elderly diabetic patients necessitate taking necessary precautions. Further studies are needed to reveal the pathophysiology of frailty in diabetic elderly patients.